The Impact Of Covid-19 Pandemic On The Economic Of Oil Palm Smallholders Household Income In Muaro Jambi District - Edison, Edison (International Journal of Science, Technology & Management, 2023)
In a two years ago, Covid-19 pandemic has caused major problems for smallholder oil palm, with an impact on the smallholder household income and biodiversity as well. Research objective is to evaluate Covid-19 pandemic impact on the smallholder's household income of oil palm that include both on-farm and off-farm sources. Research was done in the Muaro Jambi district in the beginning of 2022 and uses cross-sectional data from 120 respondents. The analytical models used in this study are qualitative and quantitative methods. The sample of pre-Covid-19 pandemic data differs from what was seen at the study site during Covid-19 pandemic, and people due to technical constraints at the study site. The important contribution of research is supporting empirical meaning of how come Covid-19 influence economic behaviour of many variable entities in Muaro Jambi smallholder farmer household income and strategic information on the impact of Covid-19 pandemic on the economy of oil palm smallholder's household income. The research result showed that there was significantly difference between average smallholder household income before Covid-19 pandemic and during Covid-19 pandemic, there was significantly differ between the average cost of smallholder household needs before Covid-19 and during Covid-19 pandemic and also there was significantly differ between the rate of smallholder household income capability. Before the Covid-19 pandemic, the income rate of smallholder households that were able to finance their consumption was about 61.67% higher than during the Covid19 pandemic, which was around 51.34%.